Perioperative Management of Subarachnoid Hemorrhage in a Patient with Alagille Syndrome and Unrepaired Tetralogy of Fallot: Case Report - Fiorda-Diaz, Juan; Shabsigh, Muhammad; Dimitrova, Galina; Soghomonyan, Suren; Sandhu, Gurneet (Frontiers in Surgery, 2017)
Alagille syndrome (ALGS) is a genetic disorder associated with multisystem dysfunction involving the hepatic, cardiovascular, and neurologic systems. Tetralogy of Fallot (TOF), a congenital cardiac anomaly, is commonly found in these patients. Patients with ALGS may also have an increased risk of cerebrovascular abnormalities and bleeding. Ruptured cerebral aneurysm and subarachnoid hemorrhage (SAH) may be developed, increasing the incidence of morbidity and mortality. Advances in neuroimaging and neurosurgery have allowed early identification and treatment of such vascular abnormalities, improving patients’ outcomes and reducing life-threatening complications such as intracranial bleeding. Authors describe the perioperative management of a patient with ALGS and TOF who was admitted to the emergency department due a ruptured intracranial aneurysm with concomitant SAH. Surgical treatment included diagnostic cerebral arteriography with coil embolization of a left posterior communicating artery aneurysm, and placement of right external ventricular drain. The combination of neuroprotective anesthetic techniques, fast emergence from anesthesia, and maintenance of intraoperative hemodynamic stability led to a successful perioperative management. A multidisciplinary approach in specialized centers is essential for the treatment of patients with SAH, especially in patients with ALGS and complex congenital heart disease such as TOF.